The castle - Mairowitz, David Zane, 1943- (SelfMadeHero, 2013)
"The protagonist, known only as K., arrives in a mountain village buried under deep snows in the middle of winter, dominated by a looming castle above it, shrouded in mist. Attempting to gain contact with the inhabitants of the castle, the officials who run the bureaucracy governing the village, K. repeatedly finds himself misunderstanding and transgressing the multitude of confusing and contradictory rules and regulations that dictate the daily life of the villagers. Kafka's atmospheric and brooding tale of extreme bureaucracy explores themes of solitude, isolation, loss, and companionship" -- from publisher's web site.